2021
DOI: 10.3390/microorganisms9071432
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Phylodynamic Analyses of HCV Strains Circulating among Patients Using Injectable Drugs in Central Italy

Abstract: Approximately 71 million people worldwide are infected with the hepatitis C virus (HCV). Injectable drug use represents the most common route of transmission in Europe and other developed countries. We studied the molecular characteristics of the HCV infection among mono-infected people who used drugs (PWUD) in Italy. Among 208 PWUD with anti-HCV antibodies, 101 (48.6%) were HCV RNA-positive, the majority (47%) were infected with the HCV genotype (Gt)1a, followed by Gt3a (34.9%), Gt4 (9.1%), Gt1b (4.5%), and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…However, median ages of all patients included in this study were overall at least 10 years higher which suggests aging of the patient population and could be attributed to long persistence of HCV infection and the relatively recent availability of the effective direct antiviral therapy. The results of previous European and national studies are concordant with our finding that GT1a and GT3a were more frequently associated with IDU [ 3 , 11 , 17 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, median ages of all patients included in this study were overall at least 10 years higher which suggests aging of the patient population and could be attributed to long persistence of HCV infection and the relatively recent availability of the effective direct antiviral therapy. The results of previous European and national studies are concordant with our finding that GT1a and GT3a were more frequently associated with IDU [ 3 , 11 , 17 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Sequence analysis of fast evolving viruses such as HCV was shown to be efficient method for viral transmission tracing [ 16 , 17 , 49 , 51 ]. Phylogenetic analysis demonstrated that 27 (9.0%) of Croatian HCV sequences had a presumed epidemiological link with another sequence and classified into 13 transmission pairs or clusters which were the most common in GT3a, while IDU was shown to be a risk factor statistically associated with clustering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One powerful variant, the episodic birth-death-sampling (EBDS) model [ 9 , 16 – 18 ] permits birth, death, and sampling rates to change in discrete epochs throughout time to capture more complicated population dynamics. Recent inference based on EBDS models has found its way already into many applications, especially on the understanding of the spread of infectious disease [ 4 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…One powerful variant, the episodic birth-death-sampling (EBDS) model (Lambert & Stadler 2013, Stadler et al 2013, Gavryushkina et al 2014, Du Plessis 2016) permits birth, death, and sampling rates to change in discrete epochs throughout time to capture more complicated population dynamics. Recent inference based on EBDS models has found its way already into many applications, especially on the understanding of the spread of infectious disease (Novitsky et al 2015, Vasylyeva et al 2020, Minosse et al 2021).…”
Section: Introductionmentioning
confidence: 99%